Biological Agent’s Effectiveness for Control of Diamondback Moth Larvae (Plutella xylostella Linn) with Different Population Levels on Lettuce - Mumtahanah, Zulfa Naila; Kristanto, Budi; Kusmiyati, Florentina (Universitas Muhammadiyah Malang, 2020)
Tritip caterpillars (Plutella xylostella) are pests that cause damage and reduce lettuce production. Control of P. xylostella pests can be done using biological agents or synthetic insecticides. Synthetic chemical pesticides in the long term can be used for resistance and resurgence of pests. Biological agents of B. bassiana, Metarhizium sp., and Trichoderma sp. can be used as an alternative solution to controlling P. xylostella. Research to examine the use of biological agents using B. bassiana, Metarhizium sp. and Trichoderma sp. to control P. xylostella attacks at different levels of pest participation. The study was conducted from 19 September to 9 November 2018 in Sidomukti, Bandungan, Semarang. The study used a completely randomized 5x3 split-plot pattern design with 3 replications. The main plot is the type of biological agents: A1: B. bassiana, A2: Metarhizium sp., A3: Trichoderma sp., A4: Insecticide and A5: control. The subplot is the pest population level: B1 = 1 larvae/plant, B2 = 2 larvae/plant, and B3 = 3 larvae/plant. Data were analyzed using ANOVA and continued with Duncan's Multiple Range Test. The results showed that biological agents and insecticides increased pest mortality, the percentage of healthy leaves, decreased the percentage of damaged leaves, the level of pest defense, and reduced the yield of lettuce.